C# 24-hour trainer complete learning package with online video tutorials - Stephens, Rod 1961- (Wrox a Wiley brand, 2016)
C# 24-Hour Trainer, Second Edition is your quick and easy guide to programming in C#, even if you have no programming experience at all. Updated to align with the latest C# standard, this book is your comprehensive beginner's guide, with each lesson supplemented by a video, for over ten hours of video training. Each chapter focuses on a specific concept or technique, with detailed, easy-to-follow explanation followed by a hands-on exercise. The goals of each exercise are outlined in advance to help you understand what you're working toward, and step-by-step instructions walk you through the operation from start to finish. Complex areas are clarified with specifically highlighted pointers that head off confusion, and additional exercises are provided so you can practice your new skills. Full instructor ancillaries are included to make this guide classroom ready, and the author's own website offers ongoing support